Women-Led Small- and Medium-Sized Enterprises During COVID-19: Examining Barriers and Opportunities. - Kevane, Michael; Ratan, Aishwarya Lakshmi; Dhar, Diva (Feminist Economics, 2024)
This study synthesizes evidence on gender dimensions of small- and medium-sized enterprises (SMEs) in low- and middle-income countries (LMICs) following the COVID-19 pandemic. Women-led SMEs are associated with lower average profits, lower revenues, fewer employees, smaller networks, and higher costs of capital. The COVID-19 pandemic exacerbated gender gaps among SMEs and undermined progress toward gender equality. To inform interventions that can support gender-intentional policy and market responses, the study builds on the conceptual model proposed by Andrea Cornwall (2016) to advance the construct of "path-dependent market dynamics," which captures how gendered social structures of market organization and behavior influence actions. Together with gendered legal discrimination, social norms, internalized behaviors, allocation of care work, mobility, and unequal access to financing, these sticky market features and dynamics can limit the effectiveness of economic recovery programs. The study suggests areas for evidence-based experimentation that can guide gender-intentional interventions for SMEs going forward. HIGHLIGHTS During the pandemic, women-led businesses experienced larger earnings losses and higher closure rates than men-led ones. Among barriers for women-led businesses, gendered structures of market organization and behavior are under-studied. Enduring gender norms can limit effectiveness of economic recovery programs. Gender-intentional enterprise programs should include evaluation components.